OPEN-AIR MUSEUM: A RETHINKING FOR INDONESIAN PARADIGM (AN OVERVIEW TOWARDS OPEN-AIR VERNACULAR HOUSES MUSEUMS IN AUSTRIA) - Yusfan Adeputera Yusran (Dimensi: Journal of Architecture and Built Environment, 2017)
Undisputedly, globalization has changed the human beings. Unexceptionally the way we live. The value of tradition is slowly fading, replaced by modern lifestyles with all its pragmatism. Traditional houses are also abandoned gradually, changed by contemporary modern houses. Then, where these traditional houses should be? Fortunately for the locals who are still committed to consistently withstand with their traditions. In contrast to other deteriorated cultural peoples, which most of them are no longer willing to dwell their inherited houses. Here, open-air museum arose to be reconsidered. Behind its controversy, open-air museum has been an answer to the phenomenon of conservation in Europe. In the midst of the controversy over the value of the place, open-air museum become a solution for European when their traditional houses increasingly burdensome in terms of maintenance. This paper aims to give an image of how Austrians preserve their traditional/vernacular houses. Six biggest open-air vernacular/traditional houses museums that dispersed on characterized-cultural region over Austria will be described comparatively here in order to give a description about the prospect for Indonesia. There are numerous principles that could be considered as guidelines, both as a theoretical framework and technical issues. Resulted recommendation could be used as hints in conserving Indonesian traditional houses in a different perspective.